How does Nutrition Affect Wound Healing? - Renner, Regina; Erfurt-Berge, Cornelia (Phlebologie, 2022)
Interference during the complex wound healing process might lead to a delayed or absence of wound closure. One possible disruptive factor can be wrong nutrition. It is necessary to differentiate between quantitative and qualitative malnutrition. Preferential obese patients suffer from a qualitative malnutrition and sarkopenia.
CRIS-Team WoS Importer:2022-07-29